IMPLEMENTASI DOKTRIN BUSINESS JUDGEMENT RULE DI INDONESIA - Hafizh Akram, Muhamad; Primadani Fanaro, Nisriina (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
The Board of Directors is one of the most important organs in a Limited Liability Company. Management of the Company that carried out by the board of directors includes running business activities, controlling, and making business decisions that have an impact on a Limited Liability Company whether the decision will cause loss or profit. In making business decisions, the Board of Directors must do so in the manner of good faith, carefully, and in accordance with the aims and objectives of the Company's establishment. If the directors already made the decision the correct manner, they cannot be held personally accountable for the decisions they make. That is what a Business judgment rules is, a doctrine that provides protection to directors to not be personally responsible if the business decisions taken cause losses to the company. Relying on a literature study, the business judgment rule is implicitly regulated in article 92 paragraph 1 and 97 paragraph 5 of Law no. 40 of 2007 regarding the Limited Liability Companies, several cases related to the business judgment rule, this article intends to analyze the implementation of the doctrine of the business judgment rule in Indonesia